ACL Graft Selection Based on Age and Sport - Mert Kahraman Marasli MD; Berte Bøe MD, PhD (Video Journal of Sports Medicine)
Background: The issue of graft selection in anterior cruciate ligament (ACL) reconstruction continues to be debated in the literature. It has been reported in the literature that different graft types give different results, especially in different demographic characteristics (age, sex) and different sports. In this study, we attempted to provide an overview of how graft selection should be made according to demographic characteristics (age, sex) and sport types. Indications: In this study, we tried to review the studies in the literature that compared graft types in ACL reconstruction according to age, sex, or type of sport. Technique Description: A narrow review of the literature was performed to compare graft selection specific to different sports. Results: There is no perfect graft selection for everyone. Given the distinct characteristics of each sport branch, including the grade of pivoting, frequency of repeated movements, and expectations, it is evident that dedicated research is required for each sport. Comparative studies on graft selection specific to each sport may increase the accuracy of the selection. Discussion/Conclusion: A review of the literature reveals a paucity of studies on the selection and outcomes of grafts in different sports. When choosing a graft for ACL reconstruction, factors such as age, sex, sport type, and expectations should be taken into consideration and a personalized decision should be made. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.